Economic Consequences of Accounting for Stock-Based Compensation - Dechow, Patricia M.; Hutton, Amy P.; Sloan, Richard G. (Journal of Accounting Research, 1996)
Patricia M. Dechow, Amy P. Hutton, Richard G. Sloan, Economic Consequences of Accounting for Stock-Based Compensation, Journal of Accounting Research, Vol. 34, Studies on Recognition, Measurement, and Disclosure Issues in Accounting (1996), pp. 1-20